Energy efficient mechanism for LoRa networks - Christos Bouras; Apostolos Gkamas; Spyridon Katsampiris (Internet of Things: Engineering Cyber Physical Human Systems, Elsevier Science, 2021, 2021)
Internet of Things (IoT) is the ability of communication between objects and refers to a wide range of applications, such as the Search and Rescue (SAR) operations. SAR applications need long distance connectivity, thus can be benefited by Low Power Wide Area Networks (LPWAN). One LPWAN technology is called LoRa (Long Range). In this context, the WeSAR project has been created that provides a system for locating and rescuing people, especially those who belong to population groups with a very high probability of getting lost. The energy consumption of the wearable devices is important factor in the SAR operations, as the battery should last more than 45 50 hours. Therefore, the proposed system is based on LoRa technology, the user localization is based on LoRa using trilateration and Time Difference of Arrival (TDoA) instead of Geolocation Positioning System (GPS), as GPS increases the energy consumption, and we created an energy-efficient mechanism to tackle the problem of energy consumption. In this paper, an energy efficient mechanism for LoRa networks is presented, that is based on the user’s state and the battery level of the wearable device. Realistic simulations have been conducted to evaluate the system for both one wearable device, and multiple wearable devices, using different mobility models. The results from the simulations have shown a decrease in the energy consumption in various node mobility models that were tested, without compromising the delivery ratio of the network, something important as the LoRa packets are used for the localization of the lost person.